Field Evaluation of Some Selected Medicinal Plants for the Treatment of Piglet Diarrhoea In Ghana (African Journal of Biomedical Research, 2020)
Piglet diarrhea is one of the major causes of huge losses facing the pig industry in West Africa. The problem of limited access to veterinary services and drugs by low-income farmers, coupled with a global rise in antibiotic resistance has necessitated research into identifying comparably efficacious, economical and readily available phytogenic extracts which could serve as alternatives to antibiotics. In this study, a field evaluation of extracts of three medicinal plants:  Picralima nitida, Ficus exasperata, and Khaya senegalensis were investigated for their individual antidiarrheal activities in management of piglet scours in Ashanti Region of Ghana. Aqueous decoctions of the stem barks of F. exasperata and K. senegalensis, and seeds of P. nitida were extracted and concentrated into 5% and 10% w/v preparations. Piglets with non-induced diarrhea were recruited and divided into groups which were treated with extracts of specific concentrations and monitored till cessation of the diarrhea. The study revealed that extracts of all three medicinal plants, in the concentrations administered, portrayed clear evidence of efficacy; and significantly inhibited the diarrheal course in the piglets. More than 70% of the subjects achieved complete cessation of the diarrhea following treatment with P. nitida 10% at 30-35 hrs; P. nitida 5% at 49-54 hrs; F. exasperata 10% at 54-59 hrs;  F. exasperata 5% at 54-59 hrs; and K. senegalensis 10% at 49-54 hours.  Comparatively, the different extracts showed varying degrees of efficiency in the treatment of diarrhoea in piglets; and the highest efficiency and potency was with P. nitida 10%